The Urban Forest Cultivating Green Infrastructure for People and the Environment - Pearlmutter, David; Calfapietra, Carlo; Samson, Roeland; O'Brien, Liz.; Krajter Ostoić, Silvija; Sanesi, Giovanni; Alonso del Amo, Rocío; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on urban "green infrastructure" - the interconnected web of vegetated spaces like street trees, parks and peri-urban forests that provide essential ecosystem services in cities. The green infrastructure approach embodies the idea that these services, such as storm-water runoff control, pollutant filtration and amenities for outdoor recreation, are just as vital for a modern city as those provided by any other type of infrastructure. Ensuring that these ecosystem services are indeed delivered in an equitable and sustainable way requires knowledge of the physical attributes of trees and urban green spaces, tools for coping with the complex social and cultural dynamics, and an understanding of how these factors can be integrated in better governance practices. By conveying the findings and recommendations of COST Action FP1204 GreenInUrbs, this volume summarizes the collaborative efforts of researchers and practitioners from across Europe to address these challenges. .
Preface -- Contributors -- 1. Environmental services provided by urban forests and green infrastructure -- 1.1. Introduction: Urban trees as environmental engineers -- 1.2. Ecosystem services: The environmental components -- 1.3. Delivery of goods and services -- 1.4. Biodiversity as support for ecosystem services and human wellbeing -- 1.5. The cost of greening: Disservices of urban trees -- 1.6. Case studies: Modeling the atmospheric benefits of urban greening -- 1.7. Assessing the ecosystem services deliverable: The critical role of the Urban Tree Inventory -- 1.8. Species-specific information for enhancing ecosystem services -- 1.9. Conclusions and recommendations -- 2. Socio-cultural services provided by urban forests and green infrastructure -- 2.1. Introduction: Socio cultural services of urban forests and green infrastructure -- 2.2. Social and environmental justice: Diversity in access to and benefits from urban green infrastructure - examples from Europe -- 2.3. Recreational use of urban green infrastructure: the tourist's perspective -- 2.4. The role and value of urban forests and green infrastructure in promoting human health and wellbeing -- 3. Economic benefits and governance of urban forests in a green infrastructure approach -- 3.1. Introduction: Governance and economic valuation -- 3.2. Challenges to governing urban green infrastructure in Europe - the case of the European Green Capital Award -- 3.3. The role of partnerships and the Third Sector in the development and delivery of urban forestry and green infrastructure -- 3.4. The Value of Valuing: Recognising the benefits of the Urban Forest -- 4. Summary -- 4.1. Introduction: Tying it all together -- 4.2. Linking the environmental, social and economic aspects of urban forestry and green infrastructure -- 4.3. Growing the Urban Forest: our Practitioners' Perspective -- Subject index. .
Keywords: Earth sciences; Life sciences; Environment; Social sciences; Earth Sciences; Life Sciences; Environmental Sciences; Society